On the Resistorless Realization of Simulated Tunable Floating Lossy Inductors with Voltage Differencing Buffered Amplifiers - Tattaya Pukkalanun; Pitchayanin Moonmuang; Worapong Tangsrirat (Journal of Communications Technology and Electronics, 2021)
Alternative circuit designs concerning the simulation of floating lossy inductors using voltage differencing buffered amplifiers (VDBAs) are described. The topologies proposed here require only three VDBAs and one capacitor to simulate a floating inductance with series and parallel resistance. The simulated equivalent elements, namely equivalent resistance (Req) and equivalent inductance (Leq) are electronically controllable through the external bias currents of the VDBAs. The VDBA non-idealities including transconductance inaccuracy and voltage transfer error on the performance of the circuits has been discussed in detail. To support the theoretical analysis and demonstrate the practical workability of the proposed synthetic inductors, PSPICE simulation and experimental test results are also reported.
Keywords: Analog and Mixed-Signal Circuit Design; Advancements in Semiconductor Devices and Circuit Design; Silicon Carbide Semiconductor Technologies